(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Government of India resolved that in order to ensure greater and more effective access to information, it is required that the Freedom of Information Act, 2002 must be made more progressive, participatory and meaningful. On this issue National Advisory Council suggested certain important changes to be incorporated in the said Act to ensure smoother and greater access to information. After examining the suggestions of the National Advisory Council and others the Government decided to make number of changes in the law. In view of the significant changes proposed by the National Advisory Council and others, it was decided to repeal the Freedom of Information Act, 2002 and enact another law for providing an effective framework for effectuating the right of information recognised under Article 19 of the Constitution of India. To achieve this object, the Right to Information Bill was introduced in the Parliament.